Exploring the need for augmented reality in financial literacy materials for early childhood learners - Fitriah, Nurlaeli; Pusposari, Luthfiya Fathi; Putri, Sandy Tegariyani; Sulaiman, Ferdinandus Arifin; Herlina, Herlina (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study explores the needs of  Augmented Reality (AR) integrated in financial literacy materials for early childhood learners.  Financial literacy is an essential life skill and introducing it at an early age can foster better decision-making and long-term financial well-being. However, existing financial literacy materials for young children are often limited to basic concepts such as money and spending. This research utilizes The D efine Stage of the 4D model to assess current financial literacy understanding and identify key concepts that should be introduced to young learners. A series of analytical activities, including Front-End Analysis, Learner Analysis, Task Analysis, and Concept Analysis, were conducted with parents, teachers, and young children to gather data. The findings reveal that while children’s understanding of money and spending is adequate, concepts like sharing remain underemphasized. Additionally, the study identifies that AR technology can provide an interactive learning for children and engaging learning experiences. The concept map developed in this study outlines essential financial literacy concepts, which can be further enriched through AR to promote a deeper understanding of topics like saving, decision-making, and distinguishing between needs and wants.